Sistem Jual Beli Ikan Secara Borongan dalam Prespektif Ekonomi Islam (Studi kasus TPI Brondong) - Mafaza, Ervina; Fahrullah (Jurnal Ekonomika dan Bisnis Islam, 2021)
Buying and selling is an activity that humans do everyday as social beings. Therefore, this examination is directed to find out Islamic law in terms of wholesale fish trading at the Fish Auction Place (TPI) Brondong, Lamongan. Qualitative is one of the methods used in this research. with the strategy of perception, meeting and documentation as information gathering techniques, then the results of the research from interview respondents were examined using a clear subjective examination technique. Based on the results of the examination and discussion conducted by the researchers, it tends to be concluded that the regulation of wholesale fish sales at the Fish Auction Place (TPI) Brondong, Lamongan is in the audit of Islamic law. the wholesale system in this buying and selling transaction still contains ambiguity that is not in accordance with the teachings of Islam